Secondary prevention of venous thromboembolism: Predictors and outcomes of guideline adherence in a long-term prospective cohort study - Mertins, Tamara; Nilius, Henning; Boss, Robin; Knuchel, Matthias; Signorell, Andri; Huber, Carola A.; Blozik, Eva; Kremer Hovinga, Johanna Anna; Bachmann, Lucas M.; Nagler, Michael (Frontiers in Cardiovascular Medicine, 2022)
Background: Prevention of recurrent venous thromboembolism (VTE) is considered a main goal of VTE management. However, the extent to which physicians adhere to the recommendations from evidence-based guidelines is unknown. Aim: From a large, prospective clinical cohort, we aimed to (1) quantify the adherence of treatment recommendations to evidence-based guidelines and establish its predictors, and (2) estimate its impact on clinical outcomes and costs in patients with VTE. Methods: We included 6’243 consecutive patients with VTE treated at the university outpatient unit. Detailed clinical characteristics and treatment recommendations were recorded. Adherence of treatment recommendations to evidence-based guidelines at risk assessment was assessed in terms of duration of anticoagulant treatment. Data on death were obtained from the Swiss Central Compensation Office. Health care claims data recorded between 2014 and 2019 were retrieved from Helsana, one of the largest Swiss health insurance companies. Results: The adherence to evidence-based guidelines was 36.1%. Among patients with non-adherence, overtreatment was present in 70.1%. Significant patient-related predictors of guideline adherence were (a) age above 50 years, (b) male sex, (c) pulmonary embolism, (d) unprovoked VTE, (e) multiple VTE, (f) laboratory tests not ordered, and (g) various cardiovascular comorbidities. Non-adherence was not significantly associated with mortality, hospitalization, admission to nursing home, and costs. Conclusions: The adherence to evidence-based guidelines was low, and several unrelated predictors appeared. Although these results need to be confirmed in other settings, they highlight the need for implementation of evidence-based guidelines in clinical practice.